Delfin Fresnosa and his works: A biography and a critical edition - Erestain, Teresita E. (Animo Repository, 1991)
Delfin Fresnosa was one of the prolific short story writers of the Thirties whose works often made it to Jose Garcia Villa's annual Roll of Honor. Unlike his fellow Veronicans Francisco Arcellana and N.V.M. Gonzalez, however, Fresnosa has not received much attention from students of Philippine literature mainly because not much is known about him and only a few of his short stories have been anthologized.This study seeks to gain greater recognition for Fresnosa and his craft by presenting a literary biography and a critical edition of his extant works.In preparing the critical edition, this researcher followed closely the guidelines set for textual criticism by Fredson Bowers (1966) which Ronal McKerrow earlier demonstrated in his 5-volume critical edition of the works of Thomas Nasche (1904-1910).This edition of Fresnosa's writings is made up of 74 short stories, one novelette, 12 folktales retold/children's stories, and 18 essays. They are annotated, the annotations being data on their publications, explanations of allusions, translations of foreign and vernacular expressions, as well as collations and emendations. They are grouped according to genre and arranged chronologically. Accompanying the critical edition is an annotated bibliography of the author's works.It is hoped that the same attention given to Fresnosa be accorded other Filipino writers, particularly his fellow Veronicans. Only with the establishment of the authentic or authoritative texts can proper critical analysis and evaluation be made of their works.